Knowledge-based entrepreneurship in Estonia - Urmas Varblane; T\~onis Mets; Janita Andrijevskaja (Center for Social and Economic Research (CASE), 2010)
The importance of new firm creation in the post-Communist economies of East Central Europe (ECE) has been subject to extensive research. This paper focuses on an area of entrepreneurship which has received relatively little attention in the transition economy context but which is of particular importance for the modernization of the transition economies: knowledge-based entrepreneurship (KBE), or new firm creation in industries considered to be science-based or to use research and development (R&D) intensively. We begin by sketching the situation in Estonia's small and medium-sized business sector, then proceed to study the conditions for high-tech firm development in the country, with particular attention devoted to the development of Information and Communication Technologies (ICT), which have been of particular significance in the Estonian case, as well as the questions of finance and policy initiatives. We then turn to the analysis of a series of case studies of firms active in the areas of information technology, life sciences, and digital mapping and navigation technology. Among the issues treated are the resources and strategies involved in KBE in Estonia, the relationships (networks) of the firms in question and how they are used for knowledge acquisition, and barriers to innovation and development. In spite of a relative lack of government support, we find that overall Estonia appears to be one of the better locations for KBE in the ECE region, with rising R&D spending, a highly educated entrepreneurial class, and universities that have moved forward rapidly in the development of technology transfer support facilities. The firms studied here rely for much of their success on foreign markets; on the other hand, difficulties in internationalisation can be identified as one of the key bottlenecks for the development of Estonian KBE. In the area of business relationships and networks, academic partners dominate.
Keywords: L26; O31; O52; P27; 330; Knowledge-based economy; entrepreneurship; transition; post-communist; SMEs; Estonia; Wissensgesellschaft; Innovation; Forschung; Informationstechnik; Entrepreneurship-Ansatz; KMU; Systemtransformation; Estland